Genome-wide association analysis in asthma subjects identifies SPATS2L as a novel bronchodilator response gene. - Blanca E Himes (PLoS Genetics, 2012)
Bronchodilator response (BDR) is an important asthma phenotype that measures reversibility of airway obstruction by comparing lung function (i.e. FEV(1)) before and after the administration of a short-acting β(2)-agonist, the most common rescue medications used for the treatment of asthma. BDR also serves as a test of β(2)-agonist efficacy. BDR is a complex trait that is partly under genetic control. A genome-wide association study (GWAS) of BDR, quantified as percent change in baseline FEV(1) after administration of a β(2)-agonist, was performed with 1,644 non-Hispanic white asthmatic subjects from six drug clinical trials: CAMP, LOCCS, LODO, a medication trial conducted by Sepracor, CARE, and ACRN. Data for 469,884 single-nucleotide polymorphisms (SNPs) were used to measure the association of SNPs with BDR using a linear regression model, while adjusting for age, sex, and height. Replication of primary P-values was attempted in 501 white subjects from SARP and 550 white subjects from DAG. Experimental evidence supporting the top gene was obtained via siRNA knockdown and Western blotting analyses. The lowest overall combined P-value was 9.7E-07 for SNP rs295137, near the SPATS2L gene. Among subjects in the primary analysis, those with rs295137 TT genotype had a median BDR of 16.0 (IQR = [6.2, 32.4]), while those with CC or TC genotypes had a median BDR of 10.9 (IQR = [5.0, 22.2]). SPATS2L mRNA knockdown resulted in increased β(2)-adrenergic receptor levels. Our results suggest that SPATS2L may be an important regulator of β(2)-adrenergic receptor down-regulation and that there is promise in gaining a better understanding of the biological mechanisms of differential response to β(2)-agonists through GWAS.